Effect of divalent metal ions on the activity and stability of β‑galactosidase isolated from Kluyveromyces lactis - P.R. Adalberto; A.C. Massabni; E.C. Carmona; A.J. Goulart; D.P. Marques; R. Monti (São Paulo State University (UNESP), 2010)
In this study, it was demonstrated that β-galactosidase can be deactivated and reactivated with EDTA and divalent metal ions. The enzyme was deactivated after 20 minutes in EDTA solution. Maximal deactivation at the lowest EDTA concentration (10-3 mol.L-1) occurred in the presence of Tris-HCl buffer (pH 7.0). The enzyme recovered 50% of its initial activity after 10 minutes at Mg2+concentrations higher than 0.1 mmol.L-1. Experimental concentrations of 0.1 mmol.L-1 Mn2+ and 1.0 mmol.L-1 Co2+ were sufficient to reactivate the enzyme to around 300% of the control activity for the Mn2+ ion and nearly 100% for the Co2+ ion. The enzyme gradually lost its activity when the Co2+ concentration was 10-2 mol.L-1. Ni2+ and Zn2+ were unable to restore the catalytic activity. K m app and V max app were 1.95 ± 0.05 mmol.L-1 and 5.40 ± 0.86x10-2 mmol.min-1.mg-1, with o-NPG as substrate. Optimal temperature and pH were 34oC and 7.5. The half-life (t1/2) at 30°C was 17.5 min for the holoenzyme and 11.0 min for the apoenzyme. With respect to pH variation, the apoenzyme proved to be more sensitive than the holoenzyme.